Covalently Coupled Immunostimulant Heterodimers1. Issue 1 (20th November 2013) - Mancini, Rock J.; Tom, Janine K.; Esser‐Kahn, Aaron P.
Abstract We report increased stimulation of dendritic cells via heterodimers of immunostimulants formed at a discrete molecular distance. Many vaccines present spatially organized agonists to immune cell receptors. These receptors cluster suggesting that signaling is increased by spatial organization and receptor proximity, but this has not been directly tested for multiple, unique receptors. In this study we probe the spatial aspect of immune cell activation using heterodimers of two covalently attached immunostimulants.